2020
DOI: 10.1177/1747021820905739
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the role of attention in the identification of associativity shortcuts using a microgenetic measure of implicit shortcut use

Abstract: Many mathematics problems can be solved in different ways or by using different strategies. Good knowledge of arithmetic principles is important for identifying and using strategies that are more sophisticated. For example, the problem “6 + 38 − 35” can be solved through a shortcut strategy where the subtraction “38 − 35 = 3” is performed before the addition “3  + 6  = 9,” a strategy that is derived from the arithmetic principle of associativity. However, both children and adults make infrequent use of this sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 93 publications
(152 reference statements)
0
12
0
Order By: Relevance
“…No studies have explored working memory and switching with associativity problems, although findings from the inversion literature indicate that they may play a role (Dubé & Robinson, 2010). Attention is theoretically expected to play a role in solving inversion problems (Siegler & Araya, 2005) but there is no empirical evidence that it is important on 'a + b − c' and 'a × b ÷ c' problems (Dubé & Robinson, 2010b;Eaves et al, 2020). Further research into the role of domain-specific and domain-general skills in strategy identification and execution is therefore warranted.…”
Section: Insert Figure 1 Herementioning
confidence: 99%
See 4 more Smart Citations
“…No studies have explored working memory and switching with associativity problems, although findings from the inversion literature indicate that they may play a role (Dubé & Robinson, 2010). Attention is theoretically expected to play a role in solving inversion problems (Siegler & Araya, 2005) but there is no empirical evidence that it is important on 'a + b − c' and 'a × b ÷ c' problems (Dubé & Robinson, 2010b;Eaves et al, 2020). Further research into the role of domain-specific and domain-general skills in strategy identification and execution is therefore warranted.…”
Section: Insert Figure 1 Herementioning
confidence: 99%
“…Three studies have compared performance on conducive and non-conducive associativity problems (Eaves et al, 2019(Eaves et al, , 2020Edwards, 2013). Edwards (2013) found that self-reported shortcut use was significantly higher on 'a × b ÷ c' problems that were conducive to a shortcut than those that were not conducive.…”
Section: Measurementmentioning
confidence: 99%
See 3 more Smart Citations